2016
DOI: 10.1007/s10620-016-4212-4
|View full text |Cite
|
Sign up to set email alerts
|

Brachytherapy Using Elastin-Like Polypeptides with 131I Inhibit Tumor Growth in Rabbits with VX2 Liver Tumor

Abstract: Elastin-like polypeptide can be an ideal carrier of (131)I and have high labeling efficiency, radiochemical purity and stability. Brachytherapy using elastin-like polypeptide with (131)I for liver tumor is a useful therapy that possesses high antitumor efficacy advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Liu X et al developed a 131 I –labeled ELPs for radiotherapy and explored their antitumor effect in rabbits with VX2 liver tumors ( Liu et al, 2016 ). ELPs delivering 131 I could improve liver function and inhibit tumor growth.…”
Section: Drug-loaded Elps For Cancer Therapymentioning
confidence: 99%
“…Liu X et al developed a 131 I –labeled ELPs for radiotherapy and explored their antitumor effect in rabbits with VX2 liver tumors ( Liu et al, 2016 ). ELPs delivering 131 I could improve liver function and inhibit tumor growth.…”
Section: Drug-loaded Elps For Cancer Therapymentioning
confidence: 99%
“…A recent ultrasound-based therapy study has linked the importance of the ECM for therapy options by using microbubbles to influence the interstitial fluid pressure in this model 14 . Furthermore, it could already be shown that brachytherapy using the genetically engineered peptide polymer elastin-like polypeptide labelled with I(131) in the VX2 liver tumors has a strong labelling efficiency and thus a high antitumor effect 15 . Non-invasive magnetic resonance imaging (MRI) biomarkers could enhance the current knowledge about ECM interactions following tumor progression and therapy.…”
mentioning
confidence: 99%